A Critical Analysis Of Bacteriogenic Lactational Mastitis (Stanyadushti) And Its Management w.s.r To Kashyapa Samhita - Bhardwaj, Rachana; Panwar, Suman; Verma, Deepak; Kumar, Anoop (International Research Journal of Ayurveda & Yoga, 2021)
Lactational mastitis is a common public health issue with global burden of 2.6 to 33% of lactating women. It may or may not be accompanied with inflammation. When it is associated with bacterial infection, it may result to breast abscess as its severe complication. It is responsible for early weaning that adversely affect the nutritional status of the child as breast milk is the sole source of nutrition for a new born child. In families with limited resources and due to stigma attached to it sometimes it may lead to severe complications leaving surgery as the only option left. Various Acharyas have mentioned in their texts some specific medicinal plants that act on the disorders of stanya and work for its detoxification. Among them Acharya Kashyapa had documented a chapter on ksheerotpatti elaborating the disorders of breast milk and its management. These plants help to subside the inflammation, reduces the associated signs and symptoms like fever, pain etc and enhance the production and quality of breast milk. The literary review is prepared in the light of classical Ayurvedic texts, botany books, API, medical journals and PG/ PHD thesis available. Various researches on the drugs are collected from the sources and compiled to evaluate the current status and scope of research in future.